2007
DOI: 10.1113/jphysiol.2007.132308
|View full text |Cite
|
Sign up to set email alerts
|

Cell content of phosphatidylinositol (4,5)bisphosphate in Ehrlich mouse ascites tumour cells in response to cell volume perturbations in anisotonic and in isosmotic media

Abstract: and PtdInsP remained constant. Our results show that PtdInsP 2 is not volume sensitive per se, and moreover that the regulatory volume adjustments in Ehrlich ascites cells are not mediated by PtdInsP 2 hydrolysis and its subsequent production of second messengers. The simplest interpretation of the observed effects would be that PtdInsP 2 is controlled by ionic strength, probably via activation/inhibition of phosphoinositide-specific phosphatases/kinases. In Ehrlich ascites cells, as shown previously, the oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…In EAT cells, the steady-state volume obtained after RVD is greater than the initial cell volume (Figs. 1 and 2), which could reflect that the volume set point is elevated in cells which have undergone an RVD or RVI response (358,706). As seen in Figure 2B, the recovery after swelling in 225 mosM medium is almost complete, whereas the "missing" recovery is Ͼ20% after swelling in 150 mosM medium (358,706).…”
Section: Volume Set Pointmentioning
confidence: 86%
See 4 more Smart Citations
“…In EAT cells, the steady-state volume obtained after RVD is greater than the initial cell volume (Figs. 1 and 2), which could reflect that the volume set point is elevated in cells which have undergone an RVD or RVI response (358,706). As seen in Figure 2B, the recovery after swelling in 225 mosM medium is almost complete, whereas the "missing" recovery is Ͼ20% after swelling in 150 mosM medium (358,706).…”
Section: Volume Set Pointmentioning
confidence: 86%
“…537), and the one for which the volume-dependent changes are most widely documented. Thus the cellular PtdIns(4,5)P 2 level has been shown to increase rapidly after osmotic cell shrinkage in a variety of cell types (695, 706, 1122), and conversely, several studies have demonstrated a decrease in the cellular PtdIns(4,5)P 2 level after osmotic swelling (135,694,706). However, there are also reports describing osmotically induced changes in the cellular levels of other phosphoinositides (639,695,889,890,1023).…”
Section: Phosphoinositide Kinases and Phospholipases C And Dmentioning
confidence: 94%
See 3 more Smart Citations